1764 Kaya's Hero : A Story of Giving - Book 3 - Shaw, Janet; Farnsworth, Bill; McAliley, Susan (Middleton, WI : Pleasant Company, 2002)
In 1764, Kaya greatly admires a courageous and kind young woman in her Nez PercGe village and wants to be worthy of her respect. Includes historical notes on the winter activities of the Nez PercGe Indians, including ceremonies and crafts.
At head of title: 1764.
Keywords: Self-esteem -- Fiction; Conduct of life -- Fiction; Nez PercGe Indians -- Fiction; Indians of North America -- Fiction -- Northwest, Pacific; Northwest, Pacific -- Fiction